Sustainability and food and nutrition security: an approach on availability and access to food in the municipality of Chókwè-Gaza province, Mozambique - Domingos, Bento Sebastião; Elísio José, António; Sitoe, Eugenio da Piedade Edmundo; Filipe Francisco, Bento (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2023)
Food and nutrition insecurity is linked to poverty worldwide. Ensuring food and nutrition security is a major challenge for most families in rural Mozambique. The aim of this study was to assess the state of nutritional and food security in families residing in Chókwè Municipality. The study was conducted using semi-structured interviews with 260 families in 7 neighborhoods. The data collected was analyzed using IBM SPSS 22 static software to obtain percentage values and a food safety index. The study revealed an unstable level of food and nutritional security in the Chókwè municipality of the order of 55%. The minimum monthly household income was about MZN 4,900.00 (US76.6), an amount that does not ensure the supply of all basic consumer goods to meet families' food needs. Corn, rice, oil and tubers are among the foods most commonly consumed by low-income families in Chókwè. Most of the food consumed by the population came from peasant family production, which depends on the region's soil and climate conditions that are limiting factors in obtaining sufficient and sustainable quantities of food for consumption. Implementing existing food and nutrition security management policies in the country can help reduce the level of food insecurity in the Chókwè community.